PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI MENGGUNAKAN MODEL THINK TALK WRITE DI KELAS V SDN 40 SEI LAREH KOTA PADANG - Asahri, Putri Masayu; Suriani, Ari; Muhammadi; Sukma, Elfia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low explanation text writing skills among fifth-grade students at SDN 40 Sei Lareh, Padang, characterized by difficulties in organizing ideas, correct spelling, and limited vocabulary. This study aims to improve explanation text writing skills through the implementation of the Think Talk Write (TTW) learning model. This is a Classroom Action Research (CAR) using both qualitative and quantitative approaches, conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects were one teacher and 21 fifth-grade students. The results showed a significant improvement in every aspect. The quality of lesson planning (Teaching Module) increased from an average of 90 (Cycle I) to 95 (Cycle II). Teacher and student activities improved from the